Analisis Faktor-Faktor Yang Mempengaruhi Pola Konsumsi Produk Perikanan Oleh Masyarakat Di Kabupaten Sidoarjo, Jawa Timur - Yushinta Aristina Sanjaya; Rahmawati Rahmawati (Jurnal Gizi dan Kuliner, 2022)
Fish is protein source that can be used as an alternative to other animal-based proteins,such as meat and lamb. This is due to the presence of high nutrients, including protein, lipid,vitamins, and minerals. The intention to increase the consumption of fisheries product, eitherfresh or processed, of Indonesian people is still required, including in District of Sidoarjo, EastJava. Fisheries aspect in District of Sidoarjo is very potential, hence it influneces the rate andpattern of fisheries product consumption in this region. The objective in this research is toanalyse the pattern of fisheries product consumption in District of Sidoarjo, East Java, alongwith its influencing factors. The data was collected online by using questionnaire filled by 103respondents. The result indicated that the fisheries product consumption of people in District ofSidoarjo was quite various in accordance with age, education level, and income. Besides, therewere factors affect the fisheries consumption of people in District of Sidoarjo, namely theknowledge of fisheries product’s benefits, preference, and the use of processing methods.Kata kunci: pola konsumsi, produk perikanan, Sidoarjo